The role of human papillomavirus vaccines in cervical cancer: Prevention and treatment. (February 2018) - Bogani, Giorgio; Leone Roberti Maggiore, Umberto; Signorelli, Mauro; Martinelli, Fabio; Ditto, Antonino; Sabatucci, Ilaria; Mosca, Lavinia; Lorusso, Domenica; Raspagliesi, Francesco
Abstract: Human papillomavirus (HPV) is the most common sexually transmitted disease, worldwide. Primary prevention thorough vaccination si able to reduce the burden of HPV-related lesions. Ten years ago the Food and drug Administration (FDA) approved the first vaccine against HPV. In the last decades, growing data on safety and effectiveness have been collected. In the present review we report the current knowledge on vaccine against HPV, highlighting the current value and prospective regarding the widespread diffusion of HPV vaccines. The role of emerging therapeutic vaccines is reviewed.